Sistema Universidade Aberta do Brasil: uma avaliação da educação a distância da Universidade Federal de Santa Maria baseada em indicadores de eficiência - Saldanha, Lauren Kleinert Londero (2018)
The Federal University of Santa Maria (UFSM), over one decade, have offered courses as a distance modality within the Open University of Brazil (UAB). Generally speaking, the undergraduate and graduate lacto sensu (specialization) have already offered 26 courses, providing more than 100 editions and about 17,700 applications available. However, although there are some available information about Distance Learning (EAD), they have not organized in parameters or indicators, yet. This is a problem to better analyse the courses’ performance and/or their efficiency. From this, the study aimed an initial estimate of undergraduate and post-graduate courses in UAB at UFSM based on efficiency indicators proposed by the Coordination for the Improvement of Higher Education Personnel (Capes). It considered all course options of undergraduate and UAB postgraduate courses, from 2005 to 2017. Methodologically, quantitative and qualitative descriptive and analytical researchers were used based on information about UAB courses at UFSM in reports and to generate indicators, in order to subsequently to check the performance of them. In terms of results it can be inferred that the level of performance of UAB undergraduate and postgraduate courses at the UFSM, in relation to efficiency, was higher than the rate of high courses estimated by Capes, but when it is compared to physically present courses, it presented a slightly lower results regarding the conclusion rate. However, it should be noted that some courses had a significant performance, even compared to courses at the face-to-face modality. Results revealed a consolidation at a higher learning systems and a qualification at this type of teaching. Otherwise, even if it is not finished at all, this type of system does not work without parameters and conditions for benchmarking the performance for an appropriate validation.